Essays on market discipline in commercial and central banking - Jens Forssbæck (Copenhagen Business School (CBS), 2009)
The thesis studies how financial markets discipline commercial and central banks' behavior in various ways. In the first part, two papers test different aspects of market discipline of commercial banks' risk taking, using a dataset of several hundred banks worldwide. In the first paper, it is shown that the risk-shifting opportunity of shareholders introduced by deposit insurance depends on ownership structure and the extent of market discipline by uninsured creditors. I find that the effect of shareholder control on risk is convex, and that creditor discipline tempers this effect but has little individual influence on risk. The second paper tests the monitoring dimension of market discipline and formulates a two-step procedure which makes it possible to sidestep the common methodological problem that banks' `true' risk is unobserved. Results suggest that if the quality of institutions is sufficiently high, some market-based indicators may be more accurate measures of banks' true risk than a set of commonly used accounting-based benchmark indicators – a possibility effectively precluded by much of previous research. In the second part of the thesis, three papers study constraints on central bank behavior introduced by financial markets, using data from a set of small, open European economies during the 1980s and 1990s. The first of these papers tests how capital account liberalization and exchange-rate regime constrain monetary policy autonomy. Contrary to traditional theory, the paper finds no autonomy effect of exchange rate flexibility, whereas capital controls provided some (albeit limited) independence from innovations in foreign money market interest rates. The remaining two papers address how deregulation, innovation, and growth in domestic money markets interplay with central banks' choices of monetary policy operating procedures. The analysis of the European countries suggests that while deregulation and the emergence of short-term financial markets constrained central bank discretion and compelled increased reliance on open market operations, the paths of money market development in different countries were also partially determined by the respective central banks' decisions. In the final paper, the same framework of analysis is applied to China, which has announced its intention to rely increasingly on market operations in monetary policy. The results suggest that the disciplining effect of domestic financial markets on central bank behavior in China is so far very small, largely due to remaining de facto financial repression.
hdl:10398/7785
Keywords: 650; Finansielle markeder; Markedsadfærd; Banker